Teachers’ Experiences in Contextualising the CAPS Curriculum Life Skills in Intermediate Phase Classrooms in the Johannesburg North Region - Urshula Frazenburg; Valencia Mabalane (Richtmann Publishing, 2022)
The teaching and contextualisation of Life Skills as required by the Curriculum and Assessment Policy Statement (CAPS) document in the intermediate Grades 4-6 have been experienced differently by teachers. The CAPS requires teachers to make the curriculum and content relevant to the varied needs and lives of learners from different backgrounds. Resultantly, the paper is driven by three objectives a) exploration of teachers’ training background; b) understanding and implementation of the CAPS requirements, and c) teachers’ conceptualisation of contextualising Life Skills in the Intermediate Phase. The study employs the constructivist theory by Vygotsky and Piaget with the emphasis on knowledge construction, individually and socially. The study was qualitative in nature. Five Life Skills Intermediate Phase teachers were selected, observed, and interviewed using semi-structured interviews. The findings indicated that each teacher had different ways of interpreting and implementing the CAPS Life Skills. The experiences were both positive and negative due to many contextual factors that influenced the contextualisation of the content. Considering the findings, the study suggests that Life Skills should be prioritised in schools as are other subjects and be taught by specialist teachers. Further studies can be conducted to explore the impact of contextualisation of the Life Skills subject on the life of learners. Received: 21 April 2022 / Accepted: 28 June 2022 / Published: 5 July 2022